2018
DOI: 10.3390/coatings8060206
|View full text |Cite
|
Sign up to set email alerts
|

Surface Aging Effect on Tire/Pavement Noise Medium-Term Evolution in a Medium-Size City

Abstract: This paper presents the geo-referenced acoustical results obtained throughout the close proximity noise (CPX) technique carried out on different urban sections included within the 2017 strategic noise mapping (Directive 2002/49/CE) in Ciudad Real, a Spanish medium-sized city. The employed methodology quantifies the tire/pavement noise generated in the contact between the tire and the surface of the studied sections. Measurements were carried out in different research campaigns between 2008 and 2015 (medium-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The following step consists of the Coatings 2019, 9,298 3 of 18 transformation of the CPX data into the required input for the traffic noise model. The developed methodology includes a propagation filter as the main improvement, compared to other attempts to study the tyre/road noise evolution and annoyance [27,28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following step consists of the Coatings 2019, 9,298 3 of 18 transformation of the CPX data into the required input for the traffic noise model. The developed methodology includes a propagation filter as the main improvement, compared to other attempts to study the tyre/road noise evolution and annoyance [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…Coatings 2019, 9, x FOR PEER REVIEW 3 of 17 methodology includes a propagation filter as the main improvement, compared to other attempts to study the tyre/road noise evolution and annoyance [27,28]. Finally, based on the traffic data and site physical characteristics for the selected case study, noise maps were created and combined with the population distribution layers from a GIS (Geographical Information System) model.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that in-vehicle noise was approximately 6 dB lower on asphalt pavement at 95.6 km/h. In a study [11], noise levels were measured using the Close ProXimity (CPX) method on six different road sections. The test vehicle had a laser profiler mounted in the front and a semi-anechoic chamber with a reference tire (Pirelli P6000) located in the rear.…”
Section: Pavement Condition and Vehicle Noisementioning
confidence: 99%
“…It was concluded that the noise levels were higher in 2015 due to road pavement deterioration. In a study [12], pavement-tire interaction noise levels were measured on 21 road sections using the CPX method. These sections had varying distress levels for Graded Asphalt Rubber (GGAR), Asphalt Concrete (AC), and Gap Graded Asphalt (GGA) pavement.…”
Section: Pavement Condition and Vehicle Noisementioning
confidence: 99%
“…Acoustic aging of road surfaces is a very important problem. Thus, the subject of interest for scientists is the influence of surface aging to noise, which is both practically verified [52][53][54][55] and theoretically modelled [56,57]. The Transport Research Centre (CDV) has been measuring the noise level of road surfaces using the CPX method in the Czech Republic since 2012.…”
Section: Introductionmentioning
confidence: 99%